Extracción y cuantificación de betacarotenos, clorofila A y B mediante cromatografía líquida (hplc) de la microalga dunaliella (Dunaliella salina) Y de la cianobacteria lepto (Leptolyngbya lagerheimii) - Urbano Gavilánez, María Adalixe (2025)
The objective of this study was to extract and quantify the content of beta-carotene, chlorophyll a, and chlorophyll b in the microalgae dunaliella (Dunaliella salina) and the cyanobacteria lepto (Leptolyngbya lagerheimii), using two separation methods and high-performance liquid chromatography (HPLC). The research arose due to the lack of standardized protocols at Bolívar State University for the extraction and analysis of these pigments in these organisms, which limits their sustainable use in biotechnological applications. The work was part of the CEDIA project ‘Functional diets based on carotenoids derived from microalgae to improve the productivity and health of trout (Oncorhynchus mykiss) in the early stages’, using samples provided by the University of Santa Elena Peninsula. In addition, the antioxidant capacity was evaluated using DPPH and the protein content using DUMAS for both species. The data were analyzed using multifactorial ANOVA and comparison of means at 95% confidence with respect to the mean. The results showed that the microalgae dunaliella (Dunaliella salina) had a higher protein content (11.25%) compared to the cyanobacteria lepto (Leptolyngbya lagerheimii) (9.16%). Dunaliella (Dunaliella salina) had 130.41 µmol ET/g sample, while the antioxidant capacity of the cyanobacterium lepto (Leptolyngbya lagerheimii) could not be determined. The LAP extraction method, which combines polar solvents and physical disruptors, proved to be the most effective, achieving greater cell wall disruption. With regard to pigments, the microalgae dunaliella (Dunaliella salina) exhibited higher concentrations of beta-carotene and chlorophyll b, while the cianobacteria lepto (Leptolyngbya lagerheimii) stood out in chlorophyll a. It should be noted that cyanobacteria do not contain chlorophyll b. Based on these findings, a single-dose beta-carotene powder supplement was developed from the microalgae dunaliella (Dunaliella salina).